ANALYZING 'HATE SPEECH PHENOMENON' RESEARCH IN INDONESIA: A SYSTEMATIC REVIEW - Yelly Andriani Barlian; Pikir Wisnu Wijayanto (University of Kuningan, 2021)
This study aims to analyze some hate speech phenomenon reviews in Indonesia. It compares how these two reviews are carried out to indicate how each source contributes and integrates the topic. The research uses a qualitative method with a systematic review. They were analyzed using a literature review matrix with the abstract data, such as author, years published, topic, and effects and findings. The PRISMA checklist (reporting guide for systematic review) is also applied to validate the observed systemic review. The research findings demonstrate that the clarity and transparency of the observed literature reviews need to be improved.